2008
DOI: 10.1159/000109594
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Antibacterial Resistance in <i>Staphylococcus aureus </i>Isolated in Kuwaiti Hospitals

Abstract: Objective: To investigate the prevalence of antibiotic resistance among Staphylococcus aureus isolated in Kuwaiti hospitals. Materials and Methods:S. aureus were isolated and identified following standard microbiological methods. Antibacterial susceptibility test was performed by disk diffusion and the measurement of minimum inhibitory concentration with E-test strips. Results: A total of 1,846 S. aureus isolates were analyzed from 13 hospitals between 1 March and 30 October 2005. They were isolated from 1,765… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 46 publications
6
28
0
Order By: Relevance
“…The high prevalence of multidrug resistance in MRSA observed in Bahrain is comparable to that in Saudi Arabia and Kuwait [14,18,25] . A recent study in Saudi Arabia showed that 78.8% of MRSA isolates obtained in 4 hospitals were multiresistant with a high prevalence of resistance to gentamicin, erythromycin, and oxytetracycline [14] .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The high prevalence of multidrug resistance in MRSA observed in Bahrain is comparable to that in Saudi Arabia and Kuwait [14,18,25] . A recent study in Saudi Arabia showed that 78.8% of MRSA isolates obtained in 4 hospitals were multiresistant with a high prevalence of resistance to gentamicin, erythromycin, and oxytetracycline [14] .…”
Section: Discussionmentioning
confidence: 66%
“…A recent study in Saudi Arabia showed that 78.8% of MRSA isolates obtained in 4 hospitals were multiresistant with a high prevalence of resistance to gentamicin, erythromycin, and oxytetracycline [14] . Similarly, multiresistant MRSA constituted 78% of MRSA isolates obtained in Kuwait hospitals with a high prevalence of resistance to gentamicin, kanamycin, erythromycin, tetracycline, ciprofloxacin, and fusidic acid [17,18,25] . The high prevalence of fusidic acid resistance in this study was of interest.…”
Section: Discussionmentioning
confidence: 99%
“…aureus , a frequent cause of infections in both the community and hospital, is the most common organism responsible for intravenous catheter-related infection, postoperative wound infection, septicemia, septic arthritis, and skin and soft tissue endogenous infections in hemodialysis patients [7,9,10,14,15] . A major part of dialysis-related infection is endogenous and related to the high frequency of nasal and skin carriage of S. aureus [16] .…”
Section: Discussionmentioning
confidence: 99%
“…In a study in another hospital of Shiraz, MRSA nasal carriage rate was reported to be 42.4% among hospital patients [11] , which is more than that observed in our study. However, one study has shown that the rates of MRSA isolates have increased steadily over the past decade [15] . Most of our isolates were sensitive to vancomycin, rifampin and ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…The most common species causing nosocomial infections are Methicillin-Resistant Staphylococcus aureus (MRSA). Importance of MRSAs as a pathogen has increased with the occurrence of high-level resistance to multiple antimicrobial drugs, such as co-amoxiclav, cefotaxime and gentamicin (10,11).…”
Section: Introductionmentioning
confidence: 99%